Makna Alif dalam Puisi Zikir D. Zawawi Imron dan Sajak Alif Ahmadun Yosi Herfanda - Rosalia, Sholeha; Wulandari, Yosi (Universitas Ahmad Dahlan, 2020)
Alif means the first, saying the Supreme Life and is Sturdy and has the element of fire and Alif is formed from Ulfah (closeness) ta'lif (formation). With this letter Allah mementa'lif (unite) His creation with the foundation of monotheism and ma'rifah belief in appreciation of faith and monotheism. Therefore, Alif opens certain meanings and definitions of shapes and colors that are in other letters. Then be Alif as